Bioresorbable Material in Secondary Orbital Reconstruction Surgery. (3rd February 2019) - Pan, Hui; Zhang, Zhenzhen; Tang, Weiwei; Li, Zhengkang; Deng, Yuan
Abstract : Purpose . To validate the potential of bioresorbable implantation in secondary revisional reconstruction after inadequate primary orbital fracture repair, with assessment of pre- and postoperative clinical characteristics and computed tomography image findings. Methods . A retrospective chart review was conducted on 16 consecutive patients treated for orbital fractures at Shanghai Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine, with inadequate prior surgeries between July 2010 and June 2017; patients who had suffered orbital blowout fractures had undergone primary surgeries elsewhere. Secondary repair of orbital fractures used bioresorbable material following unsatisfactory primary orbital repair. Patients' demographics, degree of enophthalmos, ocular motility, diplopia test results, primary implants, and surgical complications were reviewed. Results . All 16 patients had primary orbital implants consisting of Medpor, titanium mesh, hydroxyapatite, or poly-L-lactide. Of the 16 cases, 14 had malpositioned implants posteriorly and two had implant infections. Findings following primary surgery included enophthalmos (12/16), diplopia (9/16), intraorbital abscess (2/16), and ocular movement pain (1/16). Mean preoperative enophthalmos was 3.8 ± 0.8 mm. Secondary reconstruction resulted in a mean reduction of enophthalmos by 3.1 ± 0.9 mm (P < 0.01 ). Nine in ten patients experienced improvements in postoperative ocular motility and diplopia following secondary surgery. Intraorbital abscesses and eyeball movement-associated pain were cured. Conclusions . This study demonstrates that secondary orbital reconstruction of previously repaired orbital fractures using bioresorbable material can achieve excellent functional and aesthetic results with minimal complications. Bioresorbable material should be considered in secondary orbital reconstruction when clinically indicated.